2012
DOI: 10.1186/1471-2202-13-9
|View full text |Cite
|
Sign up to set email alerts
|

Visual laterality in dolphins: importance of the familiarity of stimuli

Abstract: BackgroundMany studies of cerebral asymmetries in different species lead, on the one hand, to a better understanding of the functions of each cerebral hemisphere and, on the other hand, to develop an evolutionary history of hemispheric laterality. Our animal model is particularly interesting because of its original evolutionary path, i.e. return to aquatic life after a terrestrial phase. The rare reports concerning visual laterality of marine mammals investigated mainly discrimination processes. As dolphins ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 56 publications
5
36
1
Order By: Relevance
“…Indian river dolphins are adapted to a more or less stable but turbid riverine environment where the auditory system is the only reliable source of information for spatial orientation. In contrast, the bottlenose dolphin and other delphinids live in open-ocean habitats [Rice, 1990] that require a high degree of locomotor activity, diving capacity, and visual orientation [Blois-Heulin et al, 2012]. In combination with a versatile acoustic communication [Dubrovsky, 2004], these adaptations may be seen as preconditions for high encephalization in marine species and, even more remarkably, in combination with high cortical neuron densities.…”
Section: Discussionmentioning
confidence: 99%
“…Indian river dolphins are adapted to a more or less stable but turbid riverine environment where the auditory system is the only reliable source of information for spatial orientation. In contrast, the bottlenose dolphin and other delphinids live in open-ocean habitats [Rice, 1990] that require a high degree of locomotor activity, diving capacity, and visual orientation [Blois-Heulin et al, 2012]. In combination with a versatile acoustic communication [Dubrovsky, 2004], these adaptations may be seen as preconditions for high encephalization in marine species and, even more remarkably, in combination with high cortical neuron densities.…”
Section: Discussionmentioning
confidence: 99%
“…), and exhibit visual laterality with respect to object familiarity (captive bottlenose dolphins, T. truncatus : Blois‐Heulin et al. ; wild striped dolphins, Stenella coeruleoalba : Siniscalchi et al. ).…”
Section: The History and Implementation Of Looking Time Paradigmsmentioning
confidence: 99%
“…The authors concluded that the RH processes high arousal independently of valence, although one alternative possibility is that anticipation of positive event may correspond to a quite ambiguous situation [68]. Following Baciadonna et al [67], one hypothesis therefore would be that lateralised processes concern intensity and not valence of the stimuli, two aspects of emotions separated in the circumplex model of Lang et al [69]. This would be in contrast to the valence theory [70] that predicts a clear impact of valence on the lateralisation of stimulus processing (see also [71,72]).…”
Section: Discussionmentioning
confidence: 99%